Bárbara Wagner, Benjamin de Burca - Five times Brazil - Mosqueira, Bernardo; Crockett, Vivian A.; Oldenborgh, Wendelien van (New Museum, 2022)
Working together for a decade, artists Bárbara Wagner (born 1980, Brazil) and Benjamin De Burca (born 1975, Germany) produce films and video installations that feature protagonists engaged in cultural production. The duo typically collaborates with nonactors to make their films, from writing scripts to staging performances on camera. The resulting works are marked by economic conditions and social tensions present in the contexts in which they are filmed, giving urgency to new forms of self-representation through voice, movement and drama.00Accompanying the exhibition at the New Museum - which focuses on projects that the artists filmed in Brazil over the past seven years, as well as a new commissioned piece featuring the theater group Coletivo Banzeiros - this volume includes a conversation between the artists and Margot Norton, as well as texts by Vivian Crockett, Bernardo Mosqueira and Wendelien van Oldenborgh. Exhibition: New Museum, New York, USA (30.06. - 09.10.2022)
Impressum: On the occasion of the exhibition "Bárbara Wagner and Benjamin de Burca: Five Times Brazil", June 30 - October 16, 2022
Keywords: Burca, Benjamin de -- 1975-; Wagner, Bárbara -- 1980-; Geschichte 2022; Video-Installation; Ausstellungskatalog -- New Museum -- 30.06.2022-16.10.2022 -- New York, NY; Bildband